A Pentecostal Response to Animistic Beliefs in Toraja, Indonesia - Febriani (Asian Journal of Pentecostal Studies, 2026)
The article examines how Pentecostal theology and ministry can engage respectfully and effectively with enduring animistic beliefs among the Toraja people of Indonesia while remaining faithful to Christian teaching. Topics include animistic cultural influences in Torajan Christianity, challenges of syncretism in Pentecostal ministry, and relational and contextual approaches to gospel engagement.